Organization of the murine Ig-related lambda 5 gene transcribed selectively in pre-B lymphocytes. - Kudo, A (1987)
lambda 5 is an immunoglobulin lambda light chain-related gene which is selectively transcribed in murine pre-B lymphocytes to yield a 1.2 kb poly(A)+ mRNA. Comparison of the nucleotide sequence of a 1 kb cDNA clone with the sequence of a genomic clone isolated from 70Z/3 murine pre-B lymphoma cells shows lambda 5 is composed of three exons spanning a 3.75 kb DNA segment. Conserved splice signal sequences at all exon/intron boundaries and the presence of a long open reading frame indicate that a functional mRNA molecule can be made. Exon I contains a cap-site and a potential ATG start codon as well as sequences encoding a signal peptide. This gene could encode a lambda 5 protein of 209 amino acids which has, however, not yet been identified. The 3' portion of exon II and all of exon III shows strong sequence homologies to J lambda L and C lambda L exons. Homology to the lambda L chain genes is lost in the 5' portion of exon II and throughout exon I. In exon I short homologies to leader sequences and to VH framework 1 sequences are seen.